Autonomy of the child in the South African context: is a 12 year old of sufficient maturity to consent to medical treatment?. Issue 1 (December 2016) - Ganya, Wandile; Kling, Sharon; Moodley, Keymanthri
Abstract Background A child is a developing person with evolving capacities that include autonomy, mental (decisional) capacity and capacity to assume responsibility. Hence, children are entitled to participatory (autonomy) rights in South Africa as observed in the Children's Act 38 of 2005. According to section 129 of the Act a child may consent to his or her own medical treatment provided that he or she is over the age of 12 years and is of sufficient maturity and decisional capacity to understand the various implications of the treatment including the risks and benefits thereof. However, the Act does not provide a definition for what qualifies as 'sufficient maturity' nor does it stipulate how health professionals ought to assess the decisional capacity of a child. In addition, South Africa is a culturally diverse country. The Western liberal notion of autonomy may not necessarily find equal prominence in the mores of people with a different worldview. Hence we demonstrate a few salient comparisons between legal liberal moral theory and African communitarianism as pertinent to the autonomy of the child. Discussion Children are rights-holders by virtue of their humanity. Their dignity as individual human persons affords them the entitlement to human rights as contemplated under the Constitution of the Republic of South Africa. However, contrary to the traditional Western notion of individual autonomous persons African societies hold a communalistic notion of person hence there is less regard for individual autonomy and rights with more emphasis on the communal good and maintaining the continuity of relationships and interdependencies shared within a community. A child considered in this view is not regarded as a full person. This implies that decisions concerning the child, including consent to medical treatment are discussed and determined by the community to which the child belongs. Lastly, in this article, we draw on the notion of capacity for responsibility to produce a pragmatic definition of sufficient maturity. Conclusion It seems reasonable to suggest a move away from a general legal age of consent for medical treatment toward more individualised, context-specific approaches in determining the maturity of a child patient to consent to medical treatment. Perhaps, decision-making with respect to consent to the medical treatment of a child belonging to a traditional African community where the notion of a person is embedded in communitarianism ought to involve the child's parents/guardians/caregivers where possible provided that the best interests of the child are awarded priority.